2018
DOI: 10.1088/1361-6463/aaf5ba
|View full text |Cite
|
Sign up to set email alerts
|

High-quality SiN x /p-GaN metal-insulator-semiconductor interface with low-density trap states

Abstract: We report on a high-quality p-GaN metal-insulator-semiconductor (MIS) capacitors with sharp interface morphology and the lowest interface trap density by using SiNx as the gate dielectric layer. Transmission electron microscopy and x-ray photoelectron spectroscopy (XPS) analysis revealed a high-quality interface morphology with the effective removal of carbon and oxygen impurities. Better than the interface properties of Al2O3, SiO2, and CaF2/p-GaN metal-oxide-semiconductor (MOS) or MIS capacitors, the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…On the other hand, as for the forward sweeps of the low and medium samples, both the maximum capacitance and the gate voltage showed a discrepancy between the experimental and ideal values that became pronounced depending on the doping conditions, suggesting a change in the density and energy distribution of hole traps near the interface. On the basis of these findings and previous reports, [19][20][21][22][23][24][25][26] it can be concluded that rather than the UHPA process, 27) the concentration of Mg atoms and/or the Fermi level of the p-GaN substrate play a decisive role in the passivation of hole traps.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…On the other hand, as for the forward sweeps of the low and medium samples, both the maximum capacitance and the gate voltage showed a discrepancy between the experimental and ideal values that became pronounced depending on the doping conditions, suggesting a change in the density and energy distribution of hole traps near the interface. On the basis of these findings and previous reports, [19][20][21][22][23][24][25][26] it can be concluded that rather than the UHPA process, 27) the concentration of Mg atoms and/or the Fermi level of the p-GaN substrate play a decisive role in the passivation of hole traps.…”
supporting
confidence: 64%
“…17,18) In contrast, there are few reports on p-type GaN MOS capacitors that had well-behaved capacitance-voltage (C-V ) characteristics. [19][20][21][22][23][24] Because of the significant number of hole traps located near the oxide/GaN interfaces, a large C-V hysteresis is usually observed for p-type MOS capacitors. 25) Even worse, the surface potential of GaN is pinned and an ideal amount of hole accumulation at the MOS interface hardly occurs regardless of the gate dielectric materials used.…”
mentioning
confidence: 99%
“…Several methods were introduced to improve the surface quality of GaN, such as using interface passivation layers, wet cleaning, and plasma treatments. [14][15][16][17][18][19] It was reported that a thin layer of high-quality gallium oxide (Ga 2 O x ) formed by surface oxidation of GaN can function as a passivation layer due to its low interface trap states density. 4,14,20,21) In comparison to the high-temperature process and other methods used to form Ga 2 O x to improve surface quality, ultraviolet/ozone (UV/O 3 ) treatment is a multifunctional low-temperature and low-cost process that can be used for surface cleaning as well as surface oxidation without inducing surface damages.…”
mentioning
confidence: 99%
“…This implied that the DF-ALD improved HfO 2 /Si interface characteristics for the aforementioned reasons. 28–30…”
Section: Resultsmentioning
confidence: 99%
“…This implied that the DF-ALD improved HfO 2 /Si interface characteristics for the aforementioned reasons. [28][29][30] Fig. 3d shows the plot of CET vs. leakage current density ( J g ) of the MOS capacitors to examine the insulating characteristics of the HfO 2 films.…”
Section: Electrical Propertiesmentioning
confidence: 99%